Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve for which equation is equivalent to the given formula:
[tex]\[ y = a(x-h)^2 + k \][/tex]
We will go through each option and see if we can transform the given formula into any of the given options.
### Option A:
[tex]\[ k = y + (x-h)^2 \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( a(x-h)^2 \)[/tex] from both sides:
[tex]\[ y - a(x-h)^2 = k \][/tex]
Clearly, this does not match with [tex]\( k = y + (x-h)^2 \)[/tex].
### Option B:
[tex]\[ x = \pm \sqrt{\frac{y-k}{a}} - h \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x-h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x-h \][/tex]
4. Add [tex]\( h \)[/tex] to both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{\frac{y - k}{a}} + h \][/tex]
So, this matches with [tex]\( x = \pm \sqrt{\frac{y-k}{a}} - h \)[/tex].
### Option C:
[tex]\[ h = x - \left(\frac{y-k}{a}\right)^2 \][/tex]
Starting again from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x-h)^2 \][/tex]
3. Notice that this step already doesn't match the desired form in Option C, so we can disregard it.
### Option D:
[tex]\[ a = \frac{y - k}{(x-h)^2} \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( (x-h)^2 \)[/tex]:
[tex]\[ a = \frac{y - k}{(x-h)^2} \][/tex]
This matches with [tex]\( a = \frac{y - k}{(x-h)^2} \)[/tex].
Thus, we can see that both Option B and Option D are correct transformations of the given formula. However, since we are asked to select the correct answer as per our previous instruction, we choose:
[tex]\[ \boxed{B} \][/tex]
Therefore, the correct answer is:
[tex]\[ x = \pm \sqrt{\frac{y-k}{a}} - h \][/tex]
[tex]\[ y = a(x-h)^2 + k \][/tex]
We will go through each option and see if we can transform the given formula into any of the given options.
### Option A:
[tex]\[ k = y + (x-h)^2 \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( a(x-h)^2 \)[/tex] from both sides:
[tex]\[ y - a(x-h)^2 = k \][/tex]
Clearly, this does not match with [tex]\( k = y + (x-h)^2 \)[/tex].
### Option B:
[tex]\[ x = \pm \sqrt{\frac{y-k}{a}} - h \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x-h)^2 \][/tex]
3. Take the square root of both sides:
[tex]\[ \sqrt{\frac{y - k}{a}} = x-h \][/tex]
4. Add [tex]\( h \)[/tex] to both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \pm \sqrt{\frac{y - k}{a}} + h \][/tex]
So, this matches with [tex]\( x = \pm \sqrt{\frac{y-k}{a}} - h \)[/tex].
### Option C:
[tex]\[ h = x - \left(\frac{y-k}{a}\right)^2 \][/tex]
Starting again from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( a \)[/tex]:
[tex]\[ \frac{y - k}{a} = (x-h)^2 \][/tex]
3. Notice that this step already doesn't match the desired form in Option C, so we can disregard it.
### Option D:
[tex]\[ a = \frac{y - k}{(x-h)^2} \][/tex]
Starting from [tex]\( y = a(x-h)^2 + k \)[/tex]:
1. Subtract [tex]\( k \)[/tex] from both sides:
[tex]\[ y - k = a(x-h)^2 \][/tex]
2. Divide both sides by [tex]\( (x-h)^2 \)[/tex]:
[tex]\[ a = \frac{y - k}{(x-h)^2} \][/tex]
This matches with [tex]\( a = \frac{y - k}{(x-h)^2} \)[/tex].
Thus, we can see that both Option B and Option D are correct transformations of the given formula. However, since we are asked to select the correct answer as per our previous instruction, we choose:
[tex]\[ \boxed{B} \][/tex]
Therefore, the correct answer is:
[tex]\[ x = \pm \sqrt{\frac{y-k}{a}} - h \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.